Perbandingan Kadar Merkuri (Hg) dan Aktivitas Antioksidan Ekstrak Metanolik Akar Eceng Gondok (Eichornia crassipes ) di Daerah Lawang dan Pasuruan - Chasan Arfisa; Anita Puspa Widiyana; Yoni Rina Bintari (Jurnal Kedokteran Komunitas (Journal of Community Medicine), 2020)
Background: Water hyacinth (Eichornia crassipes) is an aquatic plant that grows on the surface of the water and is also a high accumulator of heavy metals. E. crassipes has compounds containing sulfihydryl group which can bind to Hg. E. crassipes in Lawang and Pasuruan regions is thought to have high Hg levels which may result in the high antioxidant activity. The purpose of this research was to determine the levels of mercury and antioxidant activity in the methanol extract of water hyacinth roots in Lawang and Pasuruan. Methods: This research is an experimental research in the laboratory using water hyacinth roots in Lawang and Pasuruan areas taken by cluster sampling area. The extraction was by maceration method for 72 hours with methanol solvent. Extraction is done in 2 ways, namely using a shaker and without a shaker. Hg test was measured using atomic absorption spectrophotometry (AAS) at a maximum wavelength of 253.96 nm.. The antioxidant activity test was using 1,1-diphenyl-2-picrylhydrazyl (DPPH) method and their result was check using by Uv-Vis spectrophotometry (517 nm wavelength).Result: Hg content of the water hyacinth root extract Lawang shaker area 0.5287 ppm while without shaker 0.2207 ppm. For the Pasuruan shaker area 0.7910 ppm while without the shaker 0.7874 ppm (p <0.05). The antioxidant activity of the water hyacinth root extract of Pasuruan area was higher than that of Lawang area (p <0.05). IC50 value of Lawang samples with 334.8 ppm shakers; without shakers 205.4 ppm while Pasuruan samples with 161.94 ppm shakers; without a shaker 168.45 ppmConclusion: Macerated extraction of water hyacinth roots to Hg levels in Pasuruan area was higher than Lawang area. There is a relation between Hg levels and high antioxidant activity. The antioxidant activity of the water hyacinth root in Pasuruan area is higher than Lawang area.Keyword: Antioxidant, Water hyacinth, Lawang Malang. Pasuruan, Mercury (Hg)